Mathematics OpenStudy (anonymous):

Can someone please help me with this question? I have tried working it out several times and have gotten it wrong every time.... Here is the question...Solve t^2 + 4t = 1 quadratic formula ax^2 + bx + c = 0 t^2 + 4t – 1 = 0 OpenStudy (anonymous):

$t^2+4t=1$ $(t+2)^2+1+2^2=5$ $t+2=\pm\sqrt{5}$ $t=-2\pm\sqrt{5}$ OpenStudy (anonymous):

or use $t=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$ with $a=1,b=4,c=-1$ and get $t=\frac{-4\pm\sqrt{4^2-4\times 1\times (-1)}}{2\times 1}$ $t=\frac{-4\pm\sqrt{16+4}}{2}$ $t=\frac{-4\pm\sqrt{20}}{2}$ jimthompson5910 (jim_thompson5910):

The answers are $\large t=-2+\sqrt{5} \textrm{ or } t=-2−\sqrt{5}$ See the attached image for how I got those answers using the quadratic formula. OpenStudy (anonymous):

but then you have to "simplify" this because $\sqrt{20}=\sqrt{4\times 5}=2\sqrt{5}$ so you have $\frac{-4\pm\2\sqrt{5}}{2}=\frac{2(-2\pm\sqrt{5})}{2}=-2\pm\sqrt{5}$ OpenStudy (anonymous):

Thank you so much... I have been stuck on this one question... I have been trying to do homework and do my final exam for today... OpenStudy (anonymous):

same answer, but it is a lot easier to complete the square when the coefficient of the "middle term" is even, because then you do not have to spend all that time simplifying the radical a the end

Latest Questions ShelbiLW: A 3.0 m uniform beam of mass 15 kg is pivoted 1.0 m from the end as shown below. A 35 kg child sits 0.
6 hours ago 0 Replies 0 Medals ryleighmullins22: Answer the question below using the following amortization table. Month Principal Paid Interest Paid Balance 21 \$654.
6 hours ago 0 Replies 0 Medals Tonycoolkid21: help
6 hours ago 8 Replies 1 Medal Tonycoolkid21: help
6 hours ago 15 Replies 3 Medals Rx1nyDxyz: Help If the supply of a product increases, then the price decreases*** the price
7 hours ago 21 Replies 1 Medal shototodorokii: (not from a test/quiz)Nomenclature is governed by certain universal rules. Which
8 hours ago 0 Replies 0 Medals crispyrat: A guide to sqrt and cbrt
6 hours ago 21 Replies 3 Medals xXQuintonXx: help please(ss below)
8 hours ago 5 Replies 1 Medal ajfknkjfa: Prove that the two circles shown below are similar. (10 points) Circle C is shown with a center at negative 3, 1 and a radius of 4.
8 hours ago 3 Replies 1 Medal rxcklesskaisher: idk wdh dis is
9 hours ago 2 Replies 0 Medals